Study on Coupling of Entrepreneurial Enterprise Growth and Enterprise Network Competence Based on a Random Network Model - Sun, Muyun; Gao, Hong (International Journal of Online and Biomedical Engineering (iJOE), 2016)
In the 21st century, entrepreneurship has already become an important power in economic development, so entrepreneurial enterprises have turned into the research hotspot in academic circles. This paper establishes the benchmark model of entrepreneurial enterprises on the basis of random network model (GERT model). Modeling and simulation are conducted by a case study of actual data about entrepreneurial enterprise growth in Nanjing, showing the probability for entrepreneurial enterprises to grow into the mature period under the influence of the current enterprise network competence. Based on this, a comparison is made with the entrepreneurial enterprise growth model established. According to the modeling and simulation, the probability for entrepreneurial enterprises to grow into the mature period is increased under the influence of enterprise network competence. Therefore, suggestions of improving the enterprise network competence of entrepreneurial enterprises are proposed.